AASYS - Appointment Alert System: an open-source-based software to improve show rates in a health care unity - Peixoto, Hugo (2011)
In this paper we show a practical approach to deal with government impositions correlated with on time appointments in major healthcare facilities in Portugal. Reduce waiting time and improve quality on patient communication are two of the main objectives in this project. Information Systems can improve patient com- munication with hospitals and build a trust and better patient-caregiver relationship. New possibilities upraise with new smart phones and it is up to us to use it ac- cording to national standards and laws. We intend to establish a platform named Appointment Alert System (AASYS) that aids healthcare facilities to decrease costs correlated with calls for appointments, which indeed one of the major sources of appointment department costs. Schedule administration is taken in consideration and an user interface web page was also built. At the end we prove that an alert system based on open source soft- ware leading to short message service and email can help decrease costs and increase show rates.